Compound droughts as emergent outcomes of cascading drought propagation - Prashant Prashant; Surendra Kumar Mishra; Anil Kumar Lohani; Vijay P. Singh (Journal of Hydrology, 2026)

A holistic index for hydrological characterization of catchments - Prashant Prashant; Surendra Kumar Mishra; Anil Kumar Lohani; Vijay P. Singh (Journal of Hydrology, 2026)

Corrigendum to “Adulteration in paneer (Indian cottage cheese): A review of practices, detection, and public health implications – a critical analysis”[Food Control 187 (2026) 112163] - A. Surendra Babu; P. Sankarganesh; V. Parthasarathy; K. Rajkumar; Meenatai Gunderao Kamble (Food Control, 2026)

Human and Porcine Marginal Chordal Forces in a Vacuum Based Physiological In Vitro Mitral Valve Model - Mads V. Ancker; Sam E. Stephens; Justin T. Jack; Neil B. Ingels; Jonathan F. Wenk; Søren N. Skov; Surendra K. Chawla; Ajit. P. Yoganathan; Morten O. Jensen (Cardiovascular Engineering and Technology, 2026)
Introduction This study aimed to quantitatively investigate the role of marginal chordae of the mitral valve during static closure by analyzing the force within these chordae and its potential correlation with the transvalvular pressure. Materials and Methods Porcine (n = 10) and human (n = 4) mitral valves were mounted in a saddle-shaped annulus clamp, while an in vitro system was utilized to replicate a physiological systolic blood pressure by vacuum pressure applied to the atrial side of the valve. A Millar pressure catheter and force transducers (“C-gauges”) were used to acquire the data. Strut chordal force was recorded simultaneously with the marginal chordal force, to serve as a verification of the employed equipment. Results The marginal chordal force in porcine and human averaged to 0.012 N ± 0.008 N and 0.006 N ± 0.008 N respectively at peak systolic pressure of 120 mmHg. Additionally, a simplified finite element study was conducted and supports low marginal forces relative to intermediary chords. Discussion & Conclusion This low force calls into question the traditionally-described role of the marginal chordae in preventing mitral prolapse at closure. The chords do, however, still show signs of assisting with the leaflets’ positioning. The relationship between marginal chordal forces and transvalvular pressure varies significantly across experiments, further obfuscating their role in normal valvular function.

Adulteration in paneer (Indian cottage cheese): A review of practices, detection, and public health implications – a critical analysis - A. Surendra Babu; P. Sankarganesh; V. Parthasarathy; K. Rajkumar; Meenatai Gunderao Kamble (Food Control, 2026)

Indian Knowledge System in Scientific Research: A Holistic Approach for Human Welfare and Sustainability - Sanjay K. S. Patel; Yukta Mukhi; Amar J. Singh; Puneet Walia; Ghanshyam S. Thakur; Surendra Puri; Namita Singh; Urvashi Kuhad; Kavya Dashora; P. Gunasekaran; Ramesh C. Kuhad (Indian Journal of Microbiology, 2026)

In silico design, synthesis of a novel chalcone derivative and its in vitro and in vivo anticancer activity against colon cancer-induced mouse model - Uday Raj Sharma; Sushavan Roy; Gurubasavaraja Swamy Purawargaar Matada; Manjunatha P M; Suresh Janadri; Surendra Vada; T. Haribabu; Nageena Taj; Gayathri S V; Rohit Pal; Susovan Das; Nirmal Chanda (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Chronic inflammation in obesity and neurodegenerative diseases: exploring the link in disease onset and progression - Yogita Dhurandhar; Shubham Tomar; Ashmita Das; Jeevan Lal Prajapati; As Pee Singh; Surendra H. Bodake; Kamta P. Namdeo (Molecular Biology Reports, 2025)

Shelf-life of Bacillus subtilis and Gongronella butleri consortium in coirpith-based composting inoculum - K. Surendra Gopal; Nisha Peter; P. R. Anju; A. B. Anju (Indian Phytopathology, 2025)

Application of industrial internet of things (IIoT) in food processing industries - A. Adithi Arya; V. Parthasarathy; A. Surendra Babu; P. Sankarganesh (Trends in Food Science & Technology, 2025)

Enhancing energy storage capability for renewable energy systems through advanced cement-based supercapacitors - Caiyu Zhao; Wenkui Dong; T.M. Indra Mahlia; Long Shi; Kejin Wang; Surendra P. Shah; Wengui Li (Energy and Buildings, 2025)

Rice Transcriptomics Reveal the Genetic Determinants of An In Planta Photorespiratory Bypass: a Novel Way to Increase Biomass in C3 Plants - Parimalan Rangan; Dhammaprakash P. Wankhede; Rajkumar Subramani; Viswanathan Chinnusamy; Pooja Pathania; Arti Bartwal; Surendra K. Malik; Mirza Jaynul Baig; Anil Rai; Kuldeep Singh (Plant Molecular Biology Reporter, 2025)

Efficacy and Economic Viability of Biopolymer-Based Trichoderma as a Sustainable Alternative to Emerging Fungicides for Managing Safflower Soil-Borne Diseases - P. Surendra; Suma Moka; M. Kavya; R. D. Prasad; K. S. V. P. Chandrika; D. Murumkar; Reddy T. Rajeshwar; N. Prabhavathi; C. V. Ambadkar; L. Tandon Ashwarya (Journal of Crop Health, 2025)

Immune Mechanisms in Alzheimer’s Disease: The Role of Toll-Like Receptors Signalling - Dinisha Sharma; P. M. Manjunatha; T. Hari Babu; Arpan Dhungel; Sushree Swaraj; Suresh Janadari; Uday Raj Sharma; V. Surendra; Nageena Taj; S. V. Gayathri (Current Pharmacology Reports, 2024)

Evaluation of chicory leaf extract on chronic kidney disease model in streptozotocin-induced diabetic nephropathy - Simran Sultana; Uday Raj Sharma; Reddibathina Leela Haripriya; Athira Ramachandran; Runashree Borah; V. Surendra; T. Haribabu; S. V. Gayathri; Suresh Janadri; P. M. Manjunatha (Advances in Traditional Medicine, 2024)

Consequences of Local Conspecific Density Effects for Plant Diversity and Community Dynamics - Joseph A. LaManna; Florian Hartig; Jonathan A. Myers; Robert P. Freckleton; Matteo Detto; Akshay Surendra; Cole J. Doolittle; Bénédicte Bachelot; Robert Bagchi; Liza S. Comita; David M. DeFilippis; Nohemi Huanca‐Nunez; et al. (Ecology Letters, 2024)
Conspecific density dependence (CDD) in plant populations is widespread, most likely caused by local‐scale biotic interactions, and has potentially important implications for biodiversity, community composition, and ecosystem processes. However, progress in this important area of ecology has been hindered by differing viewpoints on CDD across subfields in ecology, lack of synthesis across CDD‐related frameworks, and misunderstandings about how empirical measurements of local CDD fit within the context of broader ecological theories on community assembly and diversity maintenance. Here, we propose a conceptual synthesis of local‐scale CDD and its causes, including species‐specific antagonistic and mutualistic interactions. First, we compare and clarify different uses of CDD and related concepts across subfields within ecology. We suggest the use of local stabilizing/destabilizing CDD to refer to the scenario where local conspecific density effects are more negative/positive than heterospecific effects. Second, we discuss different mechanisms for local stabilizing and destabilizing CDD, how those mechanisms are interrelated, and how they cut across several fields of study within ecology. Third, we place local stabilizing/destabilizing CDD within the context of broader ecological theories and discuss implications and challenges related to scaling up the effects of local CDD on populations, communities, and metacommunities. The ultimate goal of this synthesis is to provide a conceptual roadmap for researchers studying local CDD and its implications for population and community dynamics.

Rheumatoid arthritis-associated complications during pregnancy and its effect on offspring: comprehensive review - S. Rohini; Uday Raj Sharma; M. Vinutha; D. Shreelaxmi; Surendra Vada; Suresh Janandri; T. Haribabu; Nageena Taj; S. V. Gayathri; Abhishek Ghara; Manjunatha P. Mudagal (Inflammopharmacology, 2024)

Differences in iodine chemistry over the Antarctic continent - Anoop S. Mahajan; Shrutika Wagh; Rafael P. Fernandez; Surendra Singh; Silvia Bucci; Alfonso Saiz-Lopez (Polar Science, 2024)

Study on activation of fluorogypsum by sodium sulfate and sodium nitrite - Jianping Zhu; Zuolin Wang; Xuemao Guan; Surendra P. Shah; Haixia Liu; Huachun Yang; Wenyan Zhang (Science of The Total Environment, 2024)

Investigating an empirical approach to predict sediment yield for a design storm: a multi-site multi-variable study - Ishan Sharma; Surendra Kumar Mishra; Ashish Pandey; Henok Mekonnen Aragaw; Vijay P. Singh (Environment, Development and Sustainability, 2024)

Reinforcing efficiency of nanomaterials on mechanical and interfacial characteristics of green concrete incorporating fly ash cenosphere - Yating Zhang; Xingyi Zhu; Surendra P. Shah (Journal of Cleaner Production, 2024)

Chir pine forest and pre-monsoon drought determine spatial, and temporal patterns of forest fires in Uttarakhand Himalaya - Ripu Daman Singh; Surabhi Gumber; R. C. Sundriyal; Jeet Ram; Surendra P. Singh (Tropical Ecology, 2024)

A highly sensitive electrochemical sensor for Cr6+ ions detection using Ag NPs/rGO/quercetin modified glassy carbon electrode for water applications - G. Surendra Rajkumar; P. Senthil Kumar; Gayathri Rangasamy (Groundwater for Sustainable Development, 2024)

Variability of Particulate Amino Acids and Processes Responsible for Sources into the Coastal Waters of the Bay of Bengal - B. S. K. Kumar; D Bhaskara Rao; T. Surendra; Ch. V. Rao; M. P. Meshram (Estuaries and Coasts, 2024)

Year-long ground-based observations of bromine oxide over Bharati Station, Antarctica - Shrutika P. Wagh; Sankirna D. Joge; Surendra Singh; Prithviraj Mali; Steffen Beirle; Thomas Wagner; Silvia Bucci; Alfonso Saiz-Lopez; Rohini Bhawar; Anoop S. Mahajan (Polar Science, 2023)

Influence of slope position and aspect on the vegetation attributes and tree-water relations in forests of the central Himalayas - Vidit Tyagi; Surendra P. Singh; Ripu Daman Singh; Surabhi Gumber; Rajesh Thadani; Rajiv Pandey (Journal of Mountain Science, 2023)

Past and future rainfall change in sub-regions of Victoria, Australia - Surendra P. Rauniyar; Scott B. Power (Climatic Change, 2023)
We examine rainfall variability and change in three sub-regions of the state of Victoria in Australia: the Murray Basin Victoria (MBVic), southeast Victoria (SEVic), and southwest Victoria (SWVic). These sub-regions represent three different hydrological super-catchments over Victoria and received average cool season rainfall for the 1997–2018 period, about 15%, 11%, and 8% less, respectively, than the 1900–1959 average. All three observed declines are shown to be very unusual in terms of historical variability. On analysing CMIP5 models under different forcing conditions (preindustrial, historical-all, historical-GHGs-only, historical-natural-only, RCP2.6, RCP4.5, and RCP8.5), we estimate that external forcing caused 30% of the observed drying in SWVic, 18% in MBVic, and 17% in SEVic. The external forcing contributions to the observed trend for the 1900–2018 period are estimated to be 56%, 17%, and 24% for SWVic, MBVic, and SEVic, respectively. Taken at face value, these figures suggest that only the 1900–2018 trend in SWVic was dominated by external forcing. Nearly all models underestimate the magnitude of the observed drying. This arises because models underestimate the magnitude of decadal variability, and because models might also underestimate externally forced drying, and/or the contribution of internal variability in the real world to the observed event was unusually large. By 2037, approximately 90% of the models simulate drying in SWVic, even under a low emissions scenario. Under a high emission scenario, the anthropogenically forced drying towards the late twenty-first century is so large in all three sub-regions that internal variability appears too small to offset it.

A Procedure for Assessment of Environmental Flows Incorporating Inter- and Intra-Annual Variability in Dam-Regulated Watersheds - Ravindra Kumar Verma; Ashish Pandey; Surendra Kumar Mishra; Vijay P. Singh (Water Resources Management, 2023)

Vector competence of three species of mosquitoes to Ingwavuma virus (Manzanilla orthobunyavirus), a new bunyavirus found circulating in India - Surendra Kumar; P. R. Sreelekshmi; Y. S. Godke; A. B. Sudeep (VirusDisease, 2023)

Techno-economic Analysis of Wave Energy Resource for India - Ravi P. Patel; Garlapati Nagababu; Surendra Singh Kachhwaha; V. V. Arun Kumar Surisetty; M. Seemanth (Journal of the Indian Society of Remote Sensing, 2023)

Chir pine and banj oak responses to pre-monsoon drought across slope aspects and positions in Central Himalaya - Vidit Tyagi; Surendra P. Singh; Ripu Daman Singh; Surabhi Gumber (Environmental Monitoring and Assessment, 2023)

Estimating future rainfall distributions in a changing climate for water resource planning: Victoria, Australia - Surendra P. Rauniyar; Scott B. Power (Climate Dynamics, 2023)
Here we use observations and simulations from 40 global climate models from phase 5 of the Coupled Model Intercomparison Project (CMIP5), under preindustrial, historical, and a high emission scenario (RCP8.5) to provide estimates of Victorian cool season (April–October) rainfall for the coming century. This includes a new method which exploits recent research that estimated the relative contribution of external forcing and natural variability to the observed multidecadal decline in cool season rainfall in Victoria from 1997. The new method is aimed at removing the influence of external forcing on Victoria’s cool-season rainfall, effectively rendering a stationary time-series. The resulting historical record is then modified by scaling derived from the mean projected change evident in climate models out to 2100. The results suggest that the median value of the All-Victoria rainfall PDF will decrease monotonically over the remainder of the twenty-first century under RCP8.5. The likelihood that All-Victoria rainfall in any given year from 2025 onward will be below the observed 5th percentile of the observations (291 mm) increases monotonically, becoming three times larger by the end of the century. The new method is assessed using cross-validation and its ability to hindcast observed multidecadal rainfall change. The latter indicates that CMIP5 models poorly replicate recent interdecadal rainfall change. So, while we have more confidence in the new method because it accounts for the non-stationarity in the observed climate, limitations in the CMIP5 models results in us having low confidence in the reliability of the estimated future rainfall distributions.

Evolution of an intermediate C4 photosynthesis in the non-foliar tissues of the Poaceae - Parimalan Rangan; Dhammaprakash P. Wankhede; Rajkumar Subramani; Viswanathan Chinnusamy; Surendra K. Malik; Mirza Jaynul Baig; Kuldeep Singh; Robert Henry (Photosynthesis Research, 2022)

Bark thickness analysis of four dominant tree species of Central Himalayan forests varying in exposure to surface fires - Surabhi Gumber; Ripu Daman Singh; Jeet Ram; Ashish Tewari; Surendra P. Singh (Trees, 2022)

Vertical root distribution in Himalayan trees: about half of roots occur below 30 cm, the generally sampled depth - Girish C. Pathak; Harshita Joshi; Ripu Daman Singh; Ashish Tewari; Rajiv Pandey; Surendra P. Singh (Tropical Ecology, 2021)

A new paradigm for short-range forecasting of severe weather over the Indian region - Soma Sen Roy; Pradeep Sharma; Bikram Sen; K. Sathi Devi; S. Sunitha Devi; Neetha K. Gopal; Naresh Kumar; Krishna Mishra; Shobhit Katyar; Surendra Pratap Singh; Shibin Balakrishnan; Charan Singh; et al. (Meteorology and Atmospheric Physics, 2021)

The positive effect of pregnancy in rheumatoid arthritis and the use of medications for the management of rheumatoid arthritis during pregnancy - Uday Raj Sharma; Akhila Nediyedath Rathnakaran; B. P. Prudhvi Raj; Gayathry Padinjakkara; Akanksh Das; Surendra Vada; Manjunatha P. Mudagal (Inflammopharmacology, 2021)

Correction to: Synergies and trade-offs for climate-resilient agriculture in India: an agro-climatic zone assessment - Naveen P Singh; Bhawna Anand; Surendra Singh; S K Srivastava; Ch Srinivasa Rao; K V Rao; S K Bal (Climatic Change, 2021)

Synergies and trade-offs for climate-resilient agriculture in India: an agro-climatic zone assessment - Naveen P Singh; Bhawna Anand; Surendra Singh; S K Srivastava; Ch Srinivasa Rao; K V Rao; S K Bal (Climatic Change, 2021)

New multidimensional classification scheme of altered igneous rocks from performance comparison of isometric and modified log-ratio transformations of major elements - Surendra P. Verma; Lorena Díaz-González; M. Abdelaly Rivera-Gómez; Mauricio Rosales-Rivera (Earth Science Informatics, 2020)

Assessment of spatio-temporal vegetation dynamics in tropical arid ecosystem of India using MODIS time-series vegetation indices - Gangalakunta P. Obi Reddy; Nirmal Kumar; Nisha Sahu; Rajeev Srivastava; Surendra Kumar Singh; Lekkala Gopala Krishnama Naidu; Gajjala Ravindra Chary; Chandrashekhar M. Biradar; Murali Krishna Gumma; Bodireddy Sahadeva Reddy; Javaji Narendra Kumar (Arabian Journal of Geosciences, 2020)

G × E interactions in QTL introgression lines of Spanish-type groundnut (Arachis hypogaea L.) - A. L. Rathnakumar; Surendra S. Manohar; Hajisaheb L. Nadaf; Sudam C. Patil; Milind P. Deshmukh; P. P. Thirumalaisamy; Narendra Kumar; H. B. Lalwani; P. Nagaraju; Basavaraj Yenagi; S. S. Patil; J. Suryawanshi; et al. (Euphytica, 2020)

Comparative analysis for understanding salinity tolerance mechanism in Indian Mustard (Brassica juncea L.) - Binay K. Singh; Surendra P. Singh; Kapila Shekhawat; Sanjay S. Rathore; Avinash Pandey; Sudhir Kumar; Devendra K. Singh; Shashi Bhushan Choudhry; Saurav Kumar; Dhiraj Singh (Acta Physiologiae Plantarum, 2019)

Regional scale analysis of trends in rainfall using nonparametric methods and wavelet transforms over a semi‐arid region in India - Lalit Pal; Chandra Shekhar P. Ojha; Surendra K. Chandniha; Amit Kumar (International Journal of Climatology, 2019)
Space‐time variability of rainfall at local scale is affected by several regional factors such as aerosol concentration, greenhouse gases, land cover changes, etc., along with large scale atmospheric circulations. Predictive ability of regional circulation models can be significantly improved and efficient management of water resources can be assured by identifying dominant variables controlling spatiotemporal variations in rainfall among aforementioned factors. The present study aims to investigate dominant climate system(s) controlling trends in rainfall over Chhattisgarh state (a semi‐arid region) in India over the period of 115 years (1901–2015). Discrete wavelet transform in conjunction with Mann–Kendall test is applied to the rainfall data series at different time scales (monthly, seasonal, annual, pre‐monsoon, monsoon, post‐monsoon and winter) in order to identify the long term trends and dominant periodic components influencing the trend. In the results, negative trends are found to exist in all rainfall time series at majority of districts (except for annual and monsoon rainfall at Bijapur and Sukma district). In addition, analysis of trend in actual evapotranspiration and soil moisture in the region does not exhibits the effect of anthropogenic variables (such as land cover change, irrigation projects, etc.) on the rainfall as significant negative trend are also observed in soil moisture for majority of districts. Overall, 2‐year and 4‐year periodic components have been detected to be dominating the trends in most of the rainfall time series (annual, monsoon, post‐monsoon and winter). On comparing the identified dominating components with the existing climate systems (Atlantic multidecadal oscillations, Indian ocean dipole, Madden‐Julian oscillations, Inter‐Tropical Convergence Zone, etc.), El Niño‐Southern Oscillations has been recognized as predominant climate circulation influencing the rainfall trends over the study region. The study outcomes are expected to improve the regional precipitation forecasts and should be useful in various hydro‐meteorological analyses and decision making at regional scale.

Understanding predation behaviour of the tiger (Panthera tigris tigris) in Ranthambore tiger Reserve, Rajasthan, India: use of low-cost gel based molecular sexing of prey hairs from scats - Rahul De; Bheem Dutt Joshi; Malay Shukla; Puneet Pandey; Randeep Singh; Surendra P. Goyal (Conservation Genetics Resources, 2019)

Evaluation of nine USGS reference materials for quality control through Univariate Data Analysis System, UDASys3 - Mauricio Rosales-Rivera; Lorena Díaz-González; Surendra P. Verma (Arabian Journal of Geosciences, 2019)

Assessment of meteorological drought characteristics over Central India - Kumar Amrit; Rajendra P. Pandey; Surendra K. Mishra (Sustainable Water Resources Management, 2018)

Characteristics of meteorological droughts in northwestern India - Kumar Amrit; Rajendra P. Pandey; Surendra K. Mishra (Natural Hazards, 2018)

Evolutionary Divergence of TNL Disease-Resistant Proteins in Soybean (Glycine max) and Common Bean (Phaseolus vulgaris) - Surendra Neupane; Qin Ma; Febina M. Mathew; Adam J. Varenhorst; Ethan J. Andersen; Madhav P. Nepal (Biochemical Genetics, 2018)

Relationship of drought frequency and severity with range of annual temperature variation - Kumar Amrit; Rajendra P. Pandey; Surendra K. Mishra; Mihail Daradur (Natural Hazards, 2018)

Priority Zoning of Available Micronutrients in the Soils of Agro-ecological Sub-regions of North-East India Using Geo-spatial Techniques - Siladitya Bandyopadhyay; Prasenjit Ray; Shelton Padua; S. Ramachandran; Roomesh Kumar Jena; Partha Deb Roy; D. P. Dutta; Surendra Kumar Singh; Sanjay Kumar Ray (Agricultural Research, 2018)

Microbial and chemical quality of selected dried fish varieties available in Sri Lankan market - P. H. Ginigaddarage; I. H. W. Surendra; W. K. S. R. Weththewa; K. W. S. Ariyawansa; G. J. Ganegama Arachchi; B. K. K. K. Jinadasa; K. S. Hettiarachchi; E. M. R. K. B. Edirisinghe (Sri Lanka Journal of Aquatic Sciences, 2018)
Dried fish is one of the traditionally preserved foods in Sri Lanka.Since dried fish is often an important component of daily meal, this study was aimed to assess the quality of selected dried fish varieties in the local market. Dried fish samples of nine selected varieties were collected under three categories, viz. locally produced, imported dried fish before and after distribution to retail market. They were analyzed for microbiological and chemical parameters. Water activity of the samples was also measured. Samples were found to be negative for Escherichia coli, Staphylococcus aureus and halophilic bacteria. Aerobic Plate Count and yeast and mould count of the majority of the samples were within the acceptable limit. Histamine content exceeded 100 mg/kg level in 33% and 13% of imported and local samples respectively. Water activity of the samples was 0.05) between the analyzed parameters of all three categories.

Investigating the impacts of treated effluent discharge on coastal water health (Visakhapatnam, SW coast of Bay of Bengal, India) - Aziz Ur Rahman Shaik; Haimanti Biswas; N. Surendra Babu; N. P. C. Reddy; Z. A. Ansari (Environmental Monitoring and Assessment, 2017)

SBAS-derived TEC maps: a new tool to forecast the spatial maps of maximum probable scintillation index over India - Surendra Sunda; Sneha Yadav; R. Sridharan; M. S. Bagiya; P. V. Khekale; Pan Singh; S. V. Satish (GPS Solutions, 2017)

Evidence of microbial rhodopsins in A ntarctic D ry V alley edaphic systems - Leandro D. Guerrero; Surendra Vikram; Thulani P. Makhalanyane; Don A. Cowan (Environmental Microbiology, 2017)
Summary Microorganisms able to synthesize rhodopsins have the capacity to translocate ions through their membranes, using solar energy to generate a proton motive force. Rhodopsins are the most abundant phototrophic proteins in oceanic surface waters and are key constituents in marine bacterial ecology. However, it remains unclear how rhodopsins are used in most microorganisms. Despite their abundance in marine and fresh‐water systems, the presence of functional rhodopsin systems in edaphic habitats has never been reported. Here, we show the presence of several new putative H + , Na + and Cl + pumping rhodopsins identified by metagenomic analysis of Antarctic desert hypolithic communities. Reconstruction of two Proteobacteria genomes harboring xanthorhodopsin‐like proteins and one Bacteroidetes genome with a Na‐pumping‐like rhodopsin indicated that these bacteria were aerobic heterotrophs possessing the apparent capacity for the functional expression of rhodopsins. The existence of these protein systems in hypolithic bacteria expands the known role of rhodopsins to include terrestrial environments and suggests a possible predominant function as heterotrophic energy supply proteins, a feasible microbial adaptation to the harsh conditions prevalent in Antarctic edaphic systems.

Putative Role of Cardio Metabolic Risk Among Poorly Controlled Asthmatics in South Indian Population - Murugaiyan Sathish Babu; K. P. Sreesoorya; Surendra K. Menon; Subiman Saha; A. R. Srinivasan; S. Arul Vijaya Vani; R. Reeta; V. Kuzhandai Velu (Indian Journal of Clinical Biochemistry, 2017)

Erratum to: Quality control in geochemistry from a comparison of four central tendency and five dispersion estimators and example of a geochemical reference material - Surendra P. Verma; Lorena Díaz-González; Javier A. Pérez-Garza; Mauricio Rosales-Rivera (Arabian Journal of Geosciences, 2017)

Quality control in geochemistry from a comparison of four central tendency and five dispersion estimators and example of a geochemical reference material - Surendra P. Verma; Lorena Díaz-González; Javier A. Pérez-Garza; Mauricio Rosales-Rivera (Arabian Journal of Geosciences, 2016)

Application of a new computer program for tectonic discrimination of Cambrian to Holocene clastic sediments - Surendra P. Verma; Lorena Díaz-González; John S. Armstrong-Altrin (Earth Science Informatics, 2016)

Metagenomic analysis provides insights into functional capacity in a hyperarid desert soil niche community - Surendra Vikram; Leandro D. Guerrero; Thulani P. Makhalanyane; Phuong T. Le; Mary Seely; Don A. Cowan (Environmental Microbiology, 2016)
Summary In hyperarid ecosystems, macroscopic communities are often restricted to cryptic niches, such as hypoliths (microbial communities found beneath translucent rocks), which are widely distributed in hyperarid desert environments. While hypolithic communities are considered to play a major role in productivity, the functional guilds implicated in these processes remain unclear. Here, we describe the metagenomic sequencing, assembly and analysis of hypolithic microbial communities from the N amib D esert. Taxonomic analyses using S mall S ubunit phylogenetic markers showed that bacterial phylotypes (93%) dominated the communities, with relatively small proportions of archaea (0.43%) and fungi (5.6%). Refseq‐viral database analysis showed the presence of double stranded DNA viruses (7.8% contigs), dominated by C audovirales (59.2%). Analysis of functional genes and metabolic pathways revealed that cyanobacteria were primarily responsible for photosynthesis with the presence of multiple copies of genes for both photosystems I and II , with a smaller but significant fraction of proteobacterial anoxic photosystem II genes. Hypolithons demonstrated an extensive genetic capacity for the degradation of phosphonates and mineralization of organic sulphur. Surprisingly, we were unable to show the presence of genes representative of complete nitrogen cycles. Taken together, our analyses suggest an extensive capacity for carbon, phosphate and sulphate cycling but only limited nitrogen biogeochemistry.

Spatial and temporal variations in rainfall over Darwin and its vicinity during different large-scale environments - Surendra P. Rauniyar; Kevin J. E. Walsh (Climate Dynamics, 2016)

Precambrian crustal growth and tectonics: introduction - Vinod K. Singh; Ram Chandra; Asish R. Basu; Surendra P. Verma; Tapas K. Biswal (International Geology Review, 2015)

Plate tectonic settings for Precambrian basic rocks from Brazil by multidimensional tectonomagmatic discrimination diagrams and their limitations - Sanjeet K. Verma; Elson P. Oliveira; Surendra P. Verma (International Geology Review, 2015)

Application of 55 multi-dimensional tectonomagmatic discrimination diagrams to Precambrian belts - Surendra P. Verma; Sanjeet K. Verma; Elson P. Oliveira (International Geology Review, 2015)

Cyanoethylation of Cassia angustifolia seed gum in aqueous medium - Gaurav Rajput; I. P. Pandey; Gyanesh Joshi; Surendra S. Bisht (Journal of the Indian Academy of Wood Science, 2015)

Univariate data analysis system: deciphering mean compositions of island and continental arc magmas, and influence of the underlying crust - Surendra P. Verma; Rene Cruz-Huicochea; Lorena Díaz-González (International Geology Review, 2013)

Application of 50 multi-dimensional discrimination diagrams and significance tests: deciphering compositional similarities and differences between Hawaiian and Icelandic volcanism - Surendra P. Verma (International Geology Review, 2013)

Identification of Archaean plate tectonic processes from multidimensional discrimination diagrams and probability calculations - Sanjeet K. Verma; Surendra P. Verma (International Geology Review, 2013)

Design, synthesis, and anticonvulsant evaluation of some novel 1, 3 benzothiazol-2-yl hydrazones/acetohydrazones - Praveen Kumar; Birendra Shrivastava; Surendra N. Pandeya; Laxmi Tripathi; James P. Stables (Medicinal Chemistry Research, 2012)

Structural studies on ligand–DNA systems: A robust approach in drug design - Surat Kumar; Prateek Pandya; Kumud Pandav; Surendra P Gupta; Arun Chopra (Journal of Biosciences, 2012)

Three-dimensional temperature field simulation of a cooling of a magma chamber, La Primavera caldera, Jalisco, Mexico - Surendra P. Verma; Usy C. Arredondo-Parra; Jorge Andaverde; Efraín Gómez-Arias; Fernando J. Guerrero-Martínez (International Geology Review, 2012)

Application of the discordant outlier detection and separation system in the geosciences - Surendra P. Verma; Lorena Díaz-González (International Geology Review, 2012)

Statistical evaluation of tectonomagmatic discrimination diagrams for granitic rocks and proposal of new discriminant-function-based multi-dimensional diagrams for acid rocks - Sanjeet K. Verma; Kailasa Pandarinath; Surendra P. Verma (International Geology Review, 2012)

Search of antimycobacterial activities in hybrid molecules with benzopyran skeleton - Rama P. Tripathi; Surendra Singh Bisht; Vivek Parashar Pandey; Sarvesh K. Pandey; Shubhra Singh; Sudhir Kumar Sinha; Vinita Chaturvedi (Medicinal Chemistry Research, 2011)

Evaluation of Recent Tectonomagmatic Discrimination Diagrams and their Application to the Origin of Basic Magmas in Southern Mexico and Central America - Surendra P. Verma; Sanjeet K. Verma; Kailasa Pandarinath; María Abdelaly Rivera-Gómez (Pure and Applied Geophysics, 2011)

Application of butenonyl-C-glucosides in the synthesis of pyrazolinyl-, aminopyrimidinyl- and biphenyl methyl-β-d-C-glucopyranosides - Seerat Fatima; Vivek Parashar Pandey; Surendra Singh Bisht; Rama P. Tripathi (Molecular Diversity, 2011)

Thermal sensitivity analysis of emplacement of the magma chamber in Los Humeros caldera, Puebla, Mexico - Surendra P. Verma; Efraín Gómez-Arias; Jorge Andaverde (International Geology Review, 2011)

Pre-bleaching of mixed hardwood pulp with sulphuric acid - D. Weley Siddhartha; Pradeep Kumar; Surendra P. Singh (Journal of the Indian Academy of Wood Science, 2010)

Novel/Conceptual Floating Pulsatile System Using High Internal Phase Emulsion Based Porous Material Intended for Chronotherapy - Praveen Sher; Ganesh Ingavle; Surendra Ponrathnam; James R. Benson; Nai-Hong Li; Atmaram P. Pawar (AAPS PharmSciTech, 2009)

Comparative study of a Zn-enriched post-methanation bio-sludge and Zn sulfate as Zn sources for a rice–wheat crop rotation - Prakash C. Srivastava; Ajay P. Singh; Surendra Kumar; V. Ramachandran; Manoj Shrivastava; S. F. D’souza (Nutrient Cycling in Agroecosystems, 2009)

Modulation and Optimization of Drug Release from Uncoated Low Density Porous Carrier Based Delivery System - Praveen Sher; Ganesh Ingavle; Surendra Ponrathnam; Pankaj Poddar; Atmaram P. Pawar (AAPS PharmSciTech, 2009)

Responses of tiger (Panthera tigris) and their prey to removal of anthropogenic influences in Rajaji National Park, India - Abishek Harihar; Bivash Pandav; Surendra P. Goyal (European Journal of Wildlife Research, 2009)

Desorption and transformation of zinc in a mollisol and its uptake by plants in a rice–wheat rotation fertilized with either zinc-enriched biosludge from molasses or with inorganic zinc - Prakash C. Srivastava; Ajay P. Singh; Surendra Kumar; V. Ramachandran; Manoj Shrivastava; S. F. D’souza (Biology and Fertility of Soils, 2008)

Thyroidal regulation of substrate kinetics properties of cytochrome oxidase in rat liver mitochondria - Hiren R. Modi; Surendra S. Katyare; Samir P. Patel (Indian Journal of Clinical Biochemistry, 2008)

Thyroid Hormone-Induced Alterations in Membrane Structure-Function Relationships: Studies on Kinetic Properties of Rat Kidney Microsomal Na+,K+-ATPase and Lipid/Phospholipid Profiles - Surendra S. Katyare; Hiren R. Modi; Samir P. Patel; Minal A. Patel (The Journal of Membrane Biology, 2007)

Quantitative Bioanalytical Methods Validation and Implementation: Best Practices for Chromatographic and Ligand Binding Assays - C. T. Viswanathan; Surendra Bansal; Brian Booth; Anthony J. DeStefano; Mark J. Rose; Jeffrey Sailstad; Vinod P. Shah; Jerome P. Skelly; Patrick G. Swann; Russell Weiner (Pharmaceutical Research, 2007)

Thyroid Hormone Treatments Differentially Affect the Temperature Kinetics Properties of FoF1 ATPase and Succinate Oxidase as well as the Lipid/Phospholipid Profiles of Rat Kidney Mitochondria: A Correlative Study - Hiren R. Modi; Samir P. Patel; Surendra S. Katyare; Minal Patel (The Journal of Membrane Biology, 2007)

Workshop/conference report—Quantitative bioanalytical methods validation and implementation: Best practices for chromatographic and ligand binding assays - C. T. Viswanathan; Surendra Bansal; Brian Booth; Anthony J. DeStefano; Mark J. Rose; Jeffrey Sailstad; Vinod P. Shah; Jerome P. Skelly; Patrick G. Swann; Russell Weiner (The AAPS Journal, 2007)

Diabetic cardiomyopathy and reactive oxygen species (ROS) related parameters in male and female rats: A comparative study - Vidya Akhileshwar; Samir P. Patel; Surendra S. Katyare (Indian Journal of Clinical Biochemistry, 2007)

Discriminating four tectonic settings: Five new geochemical diagrams for basic and ultrabasic volcanic rocks based on log — ratio transformation of major-element data - Surendra P Verma; Mirna Guevara; Salil Agrawal (Journal of Earth System Science, 2006)

Effect of Alloxan Diabetes and Subsequent Insulin Treatment on Temperature Kinetics Properties of Succinate Oxidase Activity in Rat Kidney Mitochondria - Samir P. Patel; Surendra S. Katyare (The Journal of Membrane Biology, 2006)

Extension-related origin of magmas from a garnet-bearing source in the Los Tuxtlas volcanic field, Mexico - Surendra P. Verma (International Journal of Earth Sciences, 2006)

Differential pH sensitivity of tissue superoxide dismutases - Samir P Patel; Surendra S Katyare (Indian Journal of Clinical Biochemistry, 2006)

A comparative study of reactive oxygen species (ROS) related parameters in rat tissues - Samir P. Patel; Surendra S. Katyare (Indian Journal of Clinical Biochemistry, 2006)

Effect of antimalarials treatment on rat liver lysosomal function—Anin vivo study - Samir P. Patel; Subhash D. Katewa; Surendra S. Katyare (Indian Journal of Clinical Biochemistry, 2005)

Qualification of analytical instruments for use in the pharmaceutical industry: A scientific approach - Surendra K. Bansal; Thomas Layloff; Ernest D. Bush; Marta Hamilton; Edward A. Hankinson; John S. Landy; Stephen Lowes; Moheb M. Nasr; Paul A. St. Jean; Vinod P. Shah (AAPS PharmSciTech, 2004)

Qualification of analytical instruments for use in the pharmaceutical industry: A scientific approach - Surendra K. Bansal; Thomas Layloff; Ernest D. Bush; Marta Hamilton; Edward A. Hankinson; John S. Landy; Stephen Lowes; Moheb M. Nasr; Paul A. St. Jean; Vinod P. Shah (AAPS PharmSciTech, 2004)

Impact of mass mortality of a mosquito fish, Gambusia affinison the ecology of a fresh water eutrophic lake (Lake Naini Tal, India) - Surendra S. Nagdali; P. K. Gupta (Hydrobiologia, 2002)

Error propagation in equations for geochemical modeling of radiogenic isotopes in two-component mixing - Surendra P. Verma (Journal of Earth System Science, 2000)

Compilation of radiogenic isotope data in Mexico and their petrogenetic implications - Ignacio S. Torres-Alvarado; Surendra P. Verma; Gerardo Carrasco-Núñez (Journal of Earth System Science, 2000)

Bioequivalence of Topical Dermatological Dosage Forms-Methods of Evaluation of Bioequivalence - Vinod P. Shah; Gordon L. Flynn; Avraham Yacobi; Howard I. Maibach; Charles Bon; Nicholas M. Fleischer; Thomas J. Franz; Stanley A. Kaplan; Jeff Kawamoto; Lawrence J. Lesko; Jean-Paul Marty; Lynn K. Pershing; et al. (Pharmaceutical Research, 1998)